Are Friday announcements special in a continuous disclosure environment?. (18th June 2020) - Chapple, Larelle; Duong, Lien; Truong, Thu Phuong
Abstract: We re‐test the intuition that investors and traders could be preoccupied with the upcoming weekend and pay less attention to Friday corporate announcements in the continuous disclosure environment of Australia. The market reaction to Friday announcements in the US, except for earnings announcements, disappears after correcting for selection bias. However, there is no evidence of investor inattention to Friday announcements in Australia, indicating that a continuous disclosure environment improves disclosure timeliness and market efficiency. The investor attention theory is significantly challenged in a unique natural setting where the potential selection bias to delay material information release to Fridays is eliminated.